Assessment of Advanced Oxidation Protein Products and Some Biochemical Parameters in Iraqi Patients with Migraine - Salah, Ula; Al-Fayyadh, Mohanad S. (Iraqi Journal of Science, 2026)
The molecular mechanisms of migraine, a complex neurological disease, are yet unknown. The pathogenesis of migraine is thought to be influenced by oxidative stress. The presented work aims to evaluate the fasting blood sugar (FBS), advanced oxidation protein product (AOPP), homeostasis model assessment of insulin resistance (HOMA-IR), insulin, lipid profile, triglyceride-glucose index (TyG), copper, magnesium, vitamin D, potassium, and B12 vitamin in patients with migraine. The studied groups were divided into two groups: Group 1 (G1) is the healthy control group (HC) (n=50, males n=21/ females n=29). Group 2 (G2) consisted of patients with episodic migraine (n=50, males n=9/ females n=41). Results had shown that patients who have migraine had increased significance P <0.01 of AOPP, FBS, insulin, TyG, HOMA-IR, triglyceride (TG), total cholesterol (TC), very low-density lipoprotein (VLDL-C), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), copper, and potassium. Compared with control group, migraine patients had a decreased significance P < 0.01 in magnesium, vitamin B12, and vitamin D3. A negative correlation has been seen between AOPP and magnesium, vitamin B12, and vitamin D3. Meanwhile, the AOPP and other metrics have a positive correlation. In conclusion, several biochemical parameters show significant associations with migraine. This study demonstrates a significant increase in insulin resistance, lipid profile, AOPP, MDA, copper, and potassium levels in migraine patients, alongside a significant decrease in magnesium, vitamin B12, and vitamin D3 levels. Furthermore, a negative correlation was found between AOPP and magnesium, vitamin B12, and vitamin D3, while a positive correlation existed between AOPP and other biochemical